Young children's concept of their preschool teacher - Perasol, Reina Avelino; Tongson, Excelsa C. (2008)
This study aims to describe the qualities that children like of their teachers, to classify to roles portrayed by teachers in the classroom, and to categorize the school activities that young children enjoy in doing most with their teachers. Thirty preschool children participated in this study with 15 three and five-year old children coming from three different preschools in Laguna, Las Pinas City and Pasay City. The children were interviewed individually and they were asked to draw a picture of their teacher and the activity they like doing most with the teacher. Likewise, a narrative description, frequencies and percentages were also used to analyze the gathered data. The main findings of this study suggest that both three and five year old children see their teachers as Cognitive Coach - a role that engages the teacher mostly in academic activities inside the classroom. Furthermore, the kinds of activities teachers do in class and the child's earl;y experiences with the teacher help shape their concept about her. Younger children rely heavily on the color of the clothes teacher wears, material possessions such as bags, shoes and even the teacher's hairstyle. On the other hand, five-year old children's liking are based on the Psychological aspects specifically the teacher's behavioral disposition inside the classroom particularly her mental and emotional stability. Lastly, the two age-groups diferred in their responses regarding their most-liked activities they enjoy doing most with the teacher. Among three-year old children, physical activities such as dancing, singing, drawing are more appealing to them. As for the five-year old children, they found structured-academic activities such as reading, writing, working, and studying as more enjoyable.
"May 2008."
Thesis (M. Family Life and Child Development)--University of the Philippines Diliman
Keywords: Preschool children -- Philippines; Concepts in children -- Philippines